DS-CDMA system with linear multiuser detection using kasami codes (International Journal of Engineering and Computer Science, 2017)
Direct sequence code division multiple access (DS-CDMA) system suffers from Multiple Access Interference (MAI) caused by Direct Sequence users and Near–far effect. Multi-User Detection schemes are used to detect the users’ data in presence of MAI and Near-Far effect. In this we present a comparative study between linear multiuser detectors and conventional single user matched filter in DS-CDMA systems. Simulation results depict the performance of the Conventional detector, Decorrelating detector and Minimum Mean Square Error (MMSE) detector. It shows that the performance of these above mentioned detectors depends on the length of PN code used and number of users. Linear multiuser detectors perform better than the conventional matched filter detector in terms of BER performance. And in case of flat fading channel for different Doppler shifts, performance of these three detectors observed and concluded that MMSE detector has better performance than the other detectors